2018
DOI: 10.4038/jnsfsr.v46i3.8479
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of genetic diversity in sorghum genotypes of Pakistan

Abstract: Livestock and poultry production is increasing steadily in Pakistan but the production of poultry feed, cattle feed and fodder is not increasing at the same rate, and Pakistan is now facing a shortage of quality fodder and poultry feed. Sorghum is a good alternative to meet the growing fodder and poultry feed requirements. The major barrier in enhancing sorghum production is the lack of sufficient information on the genetic diversity of sorghum genotypes in Pakistan. In this study 30 sorghum genotypes from the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 8 publications
2
3
0
Order By: Relevance
“…The grain yield was observed in a range of 2858.34 Kg ha -1 to 5266.33 Kg ha -1 . These results are similar with the findings of Rakhsit et al (2012) in India (2180 Kg ha -1 to 4234 Kg ha -1 ) and Mumtaz et al (2018) in Pakistan (2562 Kg ha -1 to 5190 Kg ha -1 ). Hybrid 1 (Lasani) showed the highest grain yield, followed by hybrid 9 (YSH-95).…”
Section: G × E Genotypic Stabilitysupporting
confidence: 92%
See 1 more Smart Citation
“…The grain yield was observed in a range of 2858.34 Kg ha -1 to 5266.33 Kg ha -1 . These results are similar with the findings of Rakhsit et al (2012) in India (2180 Kg ha -1 to 4234 Kg ha -1 ) and Mumtaz et al (2018) in Pakistan (2562 Kg ha -1 to 5190 Kg ha -1 ). Hybrid 1 (Lasani) showed the highest grain yield, followed by hybrid 9 (YSH-95).…”
Section: G × E Genotypic Stabilitysupporting
confidence: 92%
“…The livestock sector is increasing in Pakistan, and grew from 191.3 Million in 2016-2017to 196.5% Million in 2017-2018 Similarly, chicken production also increased from 32.67 Million in 2016-2017to 32.91 Million in 2017-2018. The availability of fodder and feed seed was 61140 metric tons, of which 13400 metric tons were imported in 2017-2018, at considerable expense.…”
Section: Introductionmentioning
confidence: 99%
“…The first two PCs PC1 (38.01%) and PC2 (11.47%) accounted for a total of 49.47% of the total variation. This is similar to the work of Mumtaz et al [ 42 ], who reported the first two PCs of 47.88%, furthermore, Hamidou et al [ 43 ]; Andiku et al [ 27 ] reported a slightly lower value for the first two PCs of 40.72%, and 42%, respectively. The number of leaves, number of nodes, plant height, stem width, length of leaves, number of days to flowering, and length of the inflorescence are the major contributors to the variation explained by the first principal component.…”
Section: Estimation Of Variance Components Heritability and Genetic A...supporting
confidence: 90%
“…Principal component analysis (PCA) simplifies the complex data by transforming the number of correlated variables into a smaller number of variables called principal components [21]. PCA is interpreted based on the correlations among variables: the further the number from zero in either direction, the greater the positive or negative correlation [22]. PCA provides variable independence and balanced weighting of traits, which leads to an effective contribution of different characters based on respective variation [23].…”
Section: Principal Component Analysismentioning
confidence: 99%